An analysis on catalyst wettability design in strong exothermic reactions. (31st December 2021) - Tang, Yanling; Luo, Gang; Zhou, Zhiming; Li, Jianping; Gao, Guoyu; Li, Liquan; Cheng, Zhenmin
Graphical abstract: Highlights: Lyophobic modification can make gas-phase reactions occur in a three-phase system. The external wetting fraction decreases with the liquid-solid contact angle. Partial wetting is essential for strong exothermic reactions. Abstract: It would be a great advantage to keep the catalyst interior completely dry while the catalyst external surface partially wetted for a three-phase catalytic reaction system in which the reaction is between two or among more gas reactants, while the liquid only acts an inert medium for heat removal. Through such a liquid–solid interface design, gas-phase reactions with high catalyst efficiency would occur, and reaction temperature can be controlled by liquid. Hydrodynamic experiments and simulations verified that this idea can be realized by lyophobic modification of the catalyst external surface. It shows although reducing the external wetting fraction to 0 is beneficial with respect to external mass transfer, it is deficient to heat transfer. In the case of highly exothermic reactions such as ethylene oxidation to ethylene oxide, partial wetting of the catalyst surface is essential, for both providing high mass transfer rate and sufficient reaction heat removal capacity.